First-line panitumumab plus irinotecan/5-fluorouracil/leucovorin treatment in patients with metastatic colorectal cancer - Köhne, Claus-Henning; Hofheinz, Ralf-Dieter (Journal of cancer research and clinical oncology, 2012)
PurposePanitumumab monotherapy is approved for KRAS wild-type (WT) metastatic colorectal cancer (mCRC) progressing after standard chemotherapy. This study evaluated first-line panitumumab plus FOLFIRI in patients with mCRC.MethodsIn this phase II, single-arm study, panitumumab (6 mg/kg) and FOLFIRI [irinotecan (180 mg/m2) and leucovorin (400 mg/m2) followed by a 5-fluorouracil 400 mg/m2 bolus and a 2,400-3,000 mg/m2 continuous infusion] were administered every 14 days until progression. Data were analysed descriptively overall and by tumour KRAS status.Results KRAS data were available for 145/154 (94%) patients: 59% KRAS WT and 41% mutant (MT); mean follow-up was 39.5 versus 35.8 weeks, respectively. Objective responses occurred in 49% of patients: 56% versus 38% in the KRAS WT versus MT groups [(18% difference (95% CI 1-35%); odds ratio 2.1 (95% CI 1.0-4.4)]; median duration of response was 13.0 versus 7.4 months. More patients in the WT group underwent R0 resection (8% vs. 5%); median progression-free survival also favoured this group (8.9 vs. 7.2 months). The most common adverse events (any grade) were integument toxicities (98%), diarrhoea (79%) and stomatitis/oral mucositis (51%).ConclusionsAs expected, consistently favourable efficacy was observed in patients with KRAS WT versus MT tumours receiving first-line panitumumab plus FOLFIRI treatment.